Ultra-thin NaCl films as protective layers for graphene. Issue 36 (19th July 2019) - Palacio, Irene; Lauwaet, Koen; Vázquez, Luis; Palomares, Francisco Javier; González-Herrero, Héctor; Martínez, José Ignacio; Aballe, Lucía; Foerster, Michael; García-Hernández, Mar; Martín-Gago, José Ángel
Abstract : Ultra-thin NaCl layers: a potential inexpensive solution to protect graphene against ageing. Abstract : The ageing of graphene is an important issue that limits its technological applications. Capping layers are a good option for circumventing this problem. In this work, we propose the use of ultra-thin NaCl films as easily-removable protective layers. We have carried out a detailed characterization of the NaCl/graphene interface on metal substrates, namely Cu(111) and Ir(111), by means of complementary microscopy, electron diffraction and spectroscopic techniques. Interestingly, we show that NaCl neither interacts in a chemical way with graphene nor intercalates through it. We demonstrate that the NaCl film is stable under ambient conditions, protecting the graphene surface from oxidation. In addition, after removing the protective layer, graphene remains intact.